(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVE: to identify the occupational factors associated with low back pain using a surveillance tool and to characterize the low back pain by the resistance of the extensor muscles of the vertebral column among nursing professionals at an Intensive Care Unit. METHODS: Cross-sectional study. The workers answered a questionnaire about occupational factors and participated in a resistance test of the extensor muscles of the vertebral column. Associations were established through Student's T-test or Mann-Whitney's U-test and correlations using Pearson's test. RESULTS: Out of 48 participants, 32 (67%) suffered from low pain. For the resistance test, the subjects suffering from low back pain endured less time in comparison with asymptomatic subjects, but without significant differences (p=0.147). The duration of the pain episode showed a significant negative correlation (p=0.016) with the results of the resistance test though. The main factors identified as causes of low back pain were biomechanical and postural elements, conditions of the muscle structure and physical and organizational conditions. CONCLUSIONS: the main occupational factors associated with the low back pain were the posture and the characteristics of the physical and organizational conditions. In addition, the extensor muscles of the column showed a trend towards lesser resistance for workers in pain. This evidence is important when considering prevention and treatment strategies.